Evaluating User Experience of a Software Engineering Education Virtual Environment - Fernandes, Filipe A; Castro, Diego C B; Rodrigues, Claudia S C; Werner, Claudia M L (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2022)
Immersive Learning is a research topic that has the potential to improve learning outcomes. Through immersive environments, students have access to new ways of viewing and interacting, providing more engagement in learning. Therefore, the objective of this work is to present the development of a Virtual Environment (VE) prototype to support Software Engineering Education. An experimental study was carried out with 4 experts in eXtended Reality and it was found that the environment meets the purpose for which it has been designed and indicates that VE can provide satisfactory levels of VR experiences. In addition to the results, our contribution lies in evaluating the user experience in isolation since it can indicate the reduction of bias when verifying the influence of VE on learning outcomes.